Rosa Barba : The Ocean of One’s Pause - Barba, Rosa (MoMA, 2025)
For Rosa Barba, cinema “allows time and space to vibrate, collapse, overlap, and extend.” Barba’s conceptual explorations of film probe historical records, personal narratives, and the sensory experience of celluloid, often by documenting natural landscapes and human-made changes to the environment. This installation spans 15 years of Barba’s work, featuring film, kinetic sculpture, and sound. A newly commissioned work, Charge, forms the core of the installation and examines light as a source of ecological change and scientific innovation. Accompanying these works is a series of performances conceived by Barba as an “exploded poem.” In each event, the sonic frequencies of percussionist Chad Taylor, vocalist Alicia Hall Moran, and artist Rosa Barba will activate a symphony of images throughout the installation. This installation spans 15 years of Barba’s work, featuring film, kinetic sculpture, and sound. A newly commissioned work, Charge, forms the core of the installation and examines light as a source of ecological change and scientific innovation. Accompanying these works is a series of performances conceived by Barba as an “exploded poem.” In each event, the sonic frequencies of percussionist Chad Taylor, vocalist Alicia Hall Moran, and artist Rosa Barba will activate a symphony of images throughout the installation.